COVID-19 serological epidemiology study at the IG Supermarket cluster in the Special Region of Yogyakarta - Adekayanti, Putri; Subronto, Yanri Wijayanti; Ahmad, Riris Andono (Universitas Gadjah Mada, 2022)
Purpose: IG supermarkets were one of the large clusters of COVID-19 transmission in the Special Region of Yogyakarta. This study aims to determine the risk factors associated with exposure to SARS-COV-2 in the trade sector and to estimate the Secondary Attack Rate (SAR) magnitude of the COVID-19 cluster at IG Supermarkets. Methods: This study used secondary data from the RDT antibody examination results of IG Supermarket employees and notes on epidemiological investigations of close contact tracing of employees confirmed by COVID-19. The research design used descriptive and analytic observational methods with a case-control design (ratio 1:3). Results: Work unit characteristics were significantly associated with exposure to the SARS-COV-2 (p <0.05) exposure and employees who work in units that are directly related to consumers have a higher risk of reactive antibody RDT results than employees who are not directly related to consumers (OR = 3.786; 95% CI = 1.92-7. 69). The total number of close positive employee contacts with COVID-19 was 238 people (35.3% household contacts and 64.7% non-household contacts). The highest SAR was found in the household exposure setting, with an attack rate of 8.3% and a higher transmission potential in the female gender and the age group >60. Conclusion: Working in a unit with direct contact with consumers was a risk factor for exposure to SARS-COV-2 at the IG supermarket cluster in the Special Region of Yogyakarta. SAR COVID-19 was higher in household exposure settings, with a higher transmission potential at> 60 years of age. Therefore, the application of health protocols in supermarkets must be optimized to minimize the transmission of cases at home and home.